Examining social media marketing and content richness impacts on Netflix consumer satisfaction and loyalty - Muhammad Thoyib Amali; Najmi Rizki Khairani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
In a highly competitive streaming market, consumer loyalty is no longer secured by brand strength alone but requires continuous innovation and strategic differentiation. This study examines the influence of social media marketing and content richness on consumer satisfaction and loyalty among Netflix users in Indonesia. A total of 250 active Netflix subscribers participated in an online survey, and the data were analyzed using Partial Least Squares Structural Equation Modeling. The findings show that social media marketing significantly enhances consumer satisfaction but does not directly influence consumer loyalty, indicating that its impact operates indirectly through satisfaction. In contrast, content richness exerts both direct and indirect effects on satisfaction and loyalty, establishing it as the most influential factor in sustaining user commitment. Furthermore, consumer satisfaction fully mediates the relationship between social media marketing and loyalty, and partially mediates the relationship between content richness and loyalty. These results highlight satisfaction as the core mechanism linking marketing engagement and content experience to loyalty, emphasizing the importance of enhancing user experience and content quality to foster long-term retention.